An Advanced Protocol-Driven Transition from Parenteral Prostanoids to Inhaled Trepostinil in Pulmonary Arterial Hypertension. (December 2016) - Oudiz, Ronald; Agarwal, Manyoo; Rischard, Franz; De Marco, Teresa
Patients with pulmonary arterial hypertension (PAH) often require parenteral prostanoids to improve symptoms and signs of PAH. Complications of parenteral prostanoids—such as catheter-related infections and intolerable adverse effects—may develop, prompting transition to inhaled prostanoids. We report a prospective, protocol-driven transition from parenteral prostanoids to inhaled prostanoids with monitoring of exercise gas exchange and acute hemodynamics. Three PAH centers recruited patients transitioning from parenteral prostanoids to inhaled trepostinil. Rigid inclusion criteria were used, including parenteral prostanoid dose < 30 ng/kg/min, New York Heart Association functional class (FC) < 3, and pulmonary vascular resistance (PVR) < 6 Wood units. Of the 9 patients meeting initial inclusion criteria, 3 were excluded. In the remaining patients, the parenteral prostanoid was reduced and the inhaled prostanoid was increased over 24–36 hours with continuous hemodynamic monitoring. Exercise capacity and FC were measured at baseline and weeks 1, 4, and 12. All patients were successfully weaned from parenteral prostanoids. An acute PVR decrease was seen with most inhaled prostanoid doses, but PVR varied throughout the transition. Patients tolerated inhaled prostanoids for 9–12 breaths 4 times a day with no treatment-limiting adverse events. At week 12, FC was unchanged, and all patients continued to receive inhaled prostanoids without serious adverse events or additional PAH therapy. In 5 of 6 patients, 6-minute walk distance and peak V̇O2 were within 10% of baseline. Using a strict transition protocol and rigid patient selection criteria, the parenteral prostanoid to inhaled prostanoid transition appeared safe and well tolerated and did not result in clinical deterioration over 12 weeks. Hemodynamic variability noted acutely during transition in our study did not adversely affect successful transition. (Trial registration: ClinicalTrials.gov identifier: NCT01268553)